Cryo‐cooled silicon crystal monochromators: a study of power load, temperature and deformation. (8th February 2022) - Khosroabadi, Hossein; Alianelli, Lucia; Porter, Daniel G.; Collins, Steve; Sawhney, Kawal
Abstract : The heat‐load effects on cryo‐cooled Si crystals in synchrotron beamlines are investigated. Abstract : Crystal monochromators are often the primary optics in hard X‐ray synchrotron beamlines. Management of power load is central to their design. Strict requirements on stability and deformation are to be met, as new‐generation synchrotron sources deliver brighter beams of X‐rays. This article sets out to illustrate an overall picture of the deformation caused by heat load in a cryo‐cooled Si crystal monochromator using first principles. A theoretical model has been developed to predict the temperature distribution and surface deformation by applying intrinsic properties of Si material and the cooling system parameters. The model explains the universal behaviour of crystal slope error versus absorbed power; it has been benchmarked against experimental data and used to interpret finite‐element analysis of cryogenically cooled crystals.